2016
DOI: 10.1075/lab.15051.gat
|View full text |Cite
|
Sign up to set email alerts
|

Teasing apart factors influencing executive function performance in bilinguals and monolinguals at different ages

Abstract: This study attempts to tease apart a variety of factors that may contribute to performance on executive function tasks. Data from the Simon task is re-examined to determine the contributions of age, SES, language proficiency/vocabulary, general cognitive performance, and bilingualism on performance. The results suggest influence from a variety of factors, with a major contribution from relative age and from language proficiency, as measured by vocabulary. Bilingualism showed some effect in relation to older ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…One of these articles tested both preschool-aged and adolescent participants (Gathercole, Thomas, Viñas Guasch, Kennedy, Prys, Young, et al, 2016), and is also discussed in the adolescent section of our Results. As summarized in Barac, Moreno, & Bialystok, 2016;Bialystok, 1999;Bialystok & Martin, 2004, Studies 1, 2, and 3; Carlson & Meltzoff, 2008;Diaz & Farrar, 2018a;Diaz & Farrar, 2018b;Dicataldo & Roch, 2020;Gathercole et al, 2016;Goldman, Negen, & Sarnecka, 2014;Haft et al, 2019;Leikin & Tovli, 2014;Mehrani & Zabihi, 2017;Namazi & Thordardottir, 2010;Nguyen & Astington, 2014;Tran, Arredondo, & Yoshida, 2015;Tran, Arredondo, & Yoshida, 2019;Yoshida, Tran, Benitez, & Kuwabara, 2010;Yoshida, Tran, Benitez, & Kuwabara, 2011).…”
Section: Target Cognitive Abilities and Cognitive Tasks Usedmentioning
confidence: 99%
See 1 more Smart Citation
“…One of these articles tested both preschool-aged and adolescent participants (Gathercole, Thomas, Viñas Guasch, Kennedy, Prys, Young, et al, 2016), and is also discussed in the adolescent section of our Results. As summarized in Barac, Moreno, & Bialystok, 2016;Bialystok, 1999;Bialystok & Martin, 2004, Studies 1, 2, and 3; Carlson & Meltzoff, 2008;Diaz & Farrar, 2018a;Diaz & Farrar, 2018b;Dicataldo & Roch, 2020;Gathercole et al, 2016;Goldman, Negen, & Sarnecka, 2014;Haft et al, 2019;Leikin & Tovli, 2014;Mehrani & Zabihi, 2017;Namazi & Thordardottir, 2010;Nguyen & Astington, 2014;Tran, Arredondo, & Yoshida, 2015;Tran, Arredondo, & Yoshida, 2019;Yoshida, Tran, Benitez, & Kuwabara, 2010;Yoshida, Tran, Benitez, & Kuwabara, 2011).…”
Section: Target Cognitive Abilities and Cognitive Tasks Usedmentioning
confidence: 99%
“…Inhibitory control and response inhibition were assessed in 14 experiments using the child ANT (Carlson & Meltzoff, 2008), a visually cued recall task (Carlson & Meltzoff, 2008), the Kansas Reflection/Impulsivity Scale (KRISP; Carlson & Meltzoff, 2008), the Comprehensive Test of Nonverbal Intelligence (C-TONI; Carlson & Meltzoff, 2008), the Statue task (Carlson & Meltzoff, 2008), the Delay of Gratification task (Carlson & Meltzoff, 2008), Stroop and 'Strooplike' (Day/Night, Happy/Sad) tasks (Diaz & Farrar, 2018a;Diaz & Farrar, 2018b;Dicataldo & Roch, 2020;Nguyen & Astington, 2014;Tran et al, 2019), Simon Says and Bear/Dragon Simon Says tasks (Carlson & Meltzoff, 2008;Diaz & Farrar, 2018a;Diaz & Farrar, 2018b;Tran et al, 2019), the Simon task ('interference suppression', Gathercole et al, 2016;Mehrani & Zabihi, 2017), the Gift delay task (Barac et al, 2016;Carlson & Meltzoff, 2008;Tran et al, 2019), a Go/No-Go task (Barac et al, 2016), and a non-symbolic numerical discrimination task (Goldman et al, 2014). The Dimensional Change Card Sort task (DCCS) was also used to measure inhibition (Aktan-Erciyes, 2020, Studies 1 and 2; Bialystok, 1999;Bialystok & Martin, 2004, Studies 1, 2, and 3;Carlson & Meltzoff, 2008;Tran et al, 2019); this task was additionally used as a measure of cognitive flexibility in three experiments (Diaz & Farrar, 2018a;Diaz & Farrar, 2018b;Haft et al, 2019), shifting in five experiments ('switching', Aktan-Erciyes, 2020, Studies BILINGUAL CHILDHOOD COGNITIVE MEASURES 20 1 and 2; 'attention-shifting', Dicataldo & Roch, 2020...…”
Section: Bilingual Childhood Cognitive Measures 19mentioning
confidence: 99%
“…Such an advantage may be more evident in older adults, due to the general declines that come with cognitive aging, as opposed to young adults, who are at the peak of their cognitive capacity. Many early studies in this field used monolingual/bilingual comparisons and found a bilingual advantage for older adults (e.g., Bialystok, Craik, Klein, & Viswanathan, 2004; Salvatierra & Rosselli, 2011; Cox et al, 2016; Gathercole et al, 2016); notably, though, others have not found such an advantage (e.g., de Bruin, Treccani, & Della Sala, 2015; Antón, Fernández García, Carreiras, & Andoni Duñabeitia, 2016).…”
Section: Language Cognition and Agingmentioning
confidence: 99%
“…In the study by Grosse et al (2013), 33 children per age group participated. Here, we used a larger sample size to account for the fact that heterogeneous bilinguals (not all bilinguals speak the same two languages) might differ in terms of general cognitive abilities, cultural background, language similarity, language exposure, and balanced language status (Marton, 2016;Mueller Gathercole et al, 2016;Thomas-Sunesson, Hakuta, & Bialystok, 2018;Wood, Diehm, & Callender, 2016).…”
Section: Participantsmentioning
confidence: 99%